A Development of Inventory Management System for Sin Guan Leong Grocery Store - Low, Hao Xian; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2022)
Inventory management system is a very important and common system used by every store in daily life to assist in managing their inventory. However. Sin Guan Leong's Inventory management system is currently manual, and this system is inconvenient for managing grocery stores. All product records are recorded by employees in handwriting and such documents will cause problems during detection and are difficult to keep. It will also cause human error due to misunderstandings between employees. Therefore, an inventory management system for Sing Guan Leong Grocery Store is needed by helping employees manage their groceries more effectively and efficiently. This system is designed based on object oriented   approach. The methodology used is the waterfall methodology. State the user of the system… There are five modules in the system namely login module, inventory module, cashier module, supplier module and report generation module. Reports generated by the system are able to help retail store owners determine which products are selling well so that owners can refill products when the products run out. Through the system, users can record all product movements in the system systematically and store them in the system. The system is expected to provide various types of modules to help employees in retail stores more easily manage products in stores.